Effectiveness of psychological interventions in endometriosis: a systematic review with meta-analysis - del Pino-Sedeño, Tasmania; Cabrera-Maroto, María; Abrante-Luis, Alejandra; González-Hernández, Yadira; Ortíz Herrera, M Caridad (Frontiers in Psychology, 2024)
Endometriosis is a chronic gynecological disease associated with chronic debilitating pain, poor mental health and quality of life. The objective of this paper is to evaluate the effectiveness of psychological interventions aimed at improving the pain, quality of life and mental health of women with endometriosis.Methods: A systematic review (SR) of the literature with meta-analysis (MA) was carried out. MEDLINE, Embase, PsycINFO and CENTRAL were searched to locate Randomized Controlled Trials (RCTs). The risk of bias assessment of each study was conducted using the Cochrane Collaboration's RoB 2.0 tool.Seven RCTs were included (N = 757). The data obtained suggest that psychological interventions reduce dyspareunia (standardized mean difference [SMD]: -0.54, 95% CI: -0.86, -0.22) and dyschezia (mean difference [MD]: -2.90, 95% CI: -4.55, -1.26) and increase mental health levels (SMD: 0.70, 95% CI: 0. 42, 0.99); they also point to a large reduction in levels of trait anxiety (MD: -6.63, 95% CI: -8.27, -4.99) and depression (MD: -2.49, 95% CI: -3.20, -1.79), and a likely reduction in state anxiety (MD: -9.72, 95% CI: -13.11, -6.33) experienced by women with endometriosis. It was also identified that psychological interventions probably slightly reduce pelvic pain and may increase physical health. However, most of the included studies have a high overall risk of bias or have certain concerns, which limit conclusions about the certainty of the evidence.The available evidence indicates that psychological interventions are effective in improving the pain, quality of life and mental health variables of women with endometriosis.